2012
DOI: 10.1017/s0033291712001420
|View full text |Cite
|
Sign up to set email alerts
|

The balanced care model for global mental health

Abstract: The BCM refers both to a balance between hospital and community care and to a balance between all of the service components (e.g. clinical teams) that are present in any system, whether this is in low-, medium- or high-resource settings. The BCM therefore indicates that a comprehensive mental health system includes both community- and hospital-based components of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 170 publications
2
93
0
5
Order By: Relevance
“…Through shifting tasks, interventions that are originally carried out in specialized services may be carried out in primary or community care instead (van Ginneken et al, 2013). In both high-resource European countries and Syrian neighbouring countries with fewer health care resources, task-shifting is a promising strategy to implement within current stepped care or collaborative care approaches to public health (de Jong, 2011; Thornicroft & Tansella, 2013). The more widespread availability of evidence-based task-shifting interventions for common mental disorders indirectly may also have a positive impact on the treatment gap for severe psychiatric disorders and associated symptoms problems such as psychosis and suicidal behaviours in LMICs.…”
Section: Scaling-up Mental Health Interventions For Refugeesmentioning
confidence: 99%
“…Through shifting tasks, interventions that are originally carried out in specialized services may be carried out in primary or community care instead (van Ginneken et al, 2013). In both high-resource European countries and Syrian neighbouring countries with fewer health care resources, task-shifting is a promising strategy to implement within current stepped care or collaborative care approaches to public health (de Jong, 2011; Thornicroft & Tansella, 2013). The more widespread availability of evidence-based task-shifting interventions for common mental disorders indirectly may also have a positive impact on the treatment gap for severe psychiatric disorders and associated symptoms problems such as psychosis and suicidal behaviours in LMICs.…”
Section: Scaling-up Mental Health Interventions For Refugeesmentioning
confidence: 99%
“…As such, the findings of the present study align with the recommendations made recently by the National Mental Health Commission in its Report of the National Review of Mental Health Programs and Services. 1 According to several international models, [21][22][23] specialised adult mental health services should include the following components: specialised out-patient/ambulatory clinics; assertive community treatment (ACT) teams; alternatives to acute in-patient care; alternative types of long-stay community residential care; and specialised forms of work and occupation. Community-based care and living arrangements are only sustainable if located within a broader system of care that provides short-term expert acute care to manage crisis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also important to implement residential alternatives located in the community because these may be less stigmatising and more cost-effective than hospital admission. 22 A recent quasi-experimental study performed in Brisbane (Qld, Australia) demonstrated that 'crisis houses' provide a cost-effective option. 25 These services can also function as 'step-down' transitions from a period of acute psychiatric hospitalisation.…”
Section: Alternatives To Acute In-patient Carementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the 'balanced care' model (WHO 2010;Thornicroft and Tansella, 2013) balances the availability of hospital and community-based mental health services. In resource-poor settings, the model focuses on improving the recognition and treatment of people with mental illnesses within primary health care clinics, alongside the treatment of more complicated cases at specialised centres.…”
Section: Background: a Policy For Primary Mental Health Care In Southmentioning
confidence: 99%